2015
DOI: 10.3923/rjmp.2015.264.274
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inflammatory Agent Production by Ethanol Extract and Eugenol of Syzygium aromaticum (L.) Flower Bud (Clove) in LPS-Stimulated Raw 264.7 Cells

Abstract: Various plants and their derived compounds have been used in the treatment of inflammation, including Syzygium aromaticum (L.) and eugenol as one of the most active compounds in it. Inflammation is one of an important biological response to injury. Anti-inflammatory is important to treat the danger of acute and chronic inflammation. The objective of the present study was to evaluate anti-inflammatory potential of S. aromaticum flower bud (clove) ethanol extract and eugenol from S. aromaticum on LPS stimulated-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Also, it has been reported previously that PG exhibited a strong anti-inflammatory effect and were effective at inhibiting proinflammatory enzymes [44]. Many authors have reported anti-inflammatory effect of SA in experimental animal models [45-46]. However, to our knowledge, the anti-inflammatory properties of EOs combinations have not been previously targeted.…”
Section: Resultsmentioning
confidence: 98%
“…Also, it has been reported previously that PG exhibited a strong anti-inflammatory effect and were effective at inhibiting proinflammatory enzymes [44]. Many authors have reported anti-inflammatory effect of SA in experimental animal models [45-46]. However, to our knowledge, the anti-inflammatory properties of EOs combinations have not been previously targeted.…”
Section: Resultsmentioning
confidence: 98%
“…Syzygium aromaticum extract (SAE) possesses several pharmacological effects, including analgesic, antimicrobial, antitumor, anti‐inflammatory, antioxidant and cytotoxic properties. The potential anti‐inflammatory impacts of clove have also been shown by the inflammatory mediator's inhibitory activity, including IL‐1β, TNF‐α, NO, and IL‐6 (Bhowmik et al, 2012; Dibazar et al, 2015; Rodrigues et al, 2009; Rusmana et al, 2015; Singletary, 2014). Therefore, the current experiments investigated the protective effects of hydroalcoholic extract of S. aromaticum (0.25%, 0.5%, and 1% w/v) on the post‐operational‐induced PA formation in a rat model.…”
Section: Discussionmentioning
confidence: 99%